Requirement of the RNA-editing enzyme ADAR2 for normal physiology in mice - Horsch, Marion; Seeburg, Peter H.; Adler, Thure; Aguilar-Pimentel, Juan Antonio; Becker, Lore; Calzada-Wack, Julia; Garrett, Lilian; Götz, Alexander; Hans, Wolfgang; Higuchi, Miyoko; Hölter, Sabine M.; Naton, Beatrix; et al. (The journal of biological chemistry, 2011)
ADAR2, an RNA editing enzyme that converts specific adenosines to inosines in certain pre-mRNAs, often leading to amino acid substitutions in the encoded proteins, is mainly expressed in brain. Of all ADAR2-mediated edits, a single one in the pre-mRNA of the AMPA receptor subunit GluA2 is essential for survival. Hence, early postnatal death of mice lacking ADAR2 is averted when the critical edit is engineered into both GluA2 encoding Gria2 alleles. Adar2−/−/Gria2R/R mice display normal appearance and life span, but the general phenotypic effects of global lack of ADAR2 have remained unexplored. Here we have employed the Adar2−/−/Gria2R/R mouse line, and Gria2R/R mice as controls, to study the phenotypic consequences of loss of all ADAR2-mediated edits except the critical one in GluA2. Our extended phenotypic analysis covering ∼320 parameters identified significant changes related to absence of ADAR2 in behavior, hearing ability, allergy parameters and transcript profiles of brain.